Physical modelling of tsunami barrier and debris interaction - Schlesier, Hauke Günther; von Häfen, Hajo; Goseberg, Nils (Journal of Coastal and Hydraulic Structures, 2021)
Tsunami events can cause vast damage to infrastructure and human lives. A self-lifting membrane barrier was proposed to limit impacts of tsunami inundation during an event while allowing permanent access to the sea. Many aspects of this novel barrier concept have not been studied yet, including its performance under debris impact. In this context, this study investigates the interaction between a self-lifting membrane barrier and tsunami-induced debris transport. Laboratory experiments in a wave flume were carried out, in which 20 ft shipping-container models were propagated by tsunami-like waves into a model membrane barrier. Varying hydrodynamic boundary conditions and amount of debris were used to study different magnitudes of surge and debris loading. The tests showed that an increased amount of debris led to decreased surge propagation upstream the barrier. Formation of a temporally stable debris dam was prevented by the dynamic character of the barrier-debris-interaction. In total, 90% of debris transport further in land was obstructed in presence of the studied membrane barrier. The self-lifting membrane barrier retains functionality under debris-loaded surge impact.